KEDUDUKAN WANITA DI IRAN: MENGUNGKAP PANDANGAN ULAMA SYâIAH - Sadik, M. (Institut Agama Islam Negeri (IAIN) Palu, 2005)
In Iran, woman emancipation does not undergo fundamental change compared with that in other Islamic worlds. In Iran, woman are still in subordinate position. It is within this context that conservative theological thought ofÂ Shiâi ulamas (Islamic scholars), especially KhomeniÂ gave a great contribution to the subordinating ofÂ status of woman in Iran. This article tries to discussÂ status of woman in Iran from ShiâiÂ ulamaâs perspective.Â Kata Kunci: Kedudukan wanita, ulama Syiâah